The best damn cybercrime and digital forensics book period - Cardwell, Kevin (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2007)
Electronic discovery refers to a process in which electronic data is sought, located, secured, and searched with the intent of using it as evidence in a legal case. Computer forensics is the application of computer investigation and analysis techniques to perform an investigation to find out exactly what happened on a computer and who was responsible. IDC estimates that the U.S. market for computer forensics will be grow from $252 million in 2004 to $630 million by 2009. Business is strong outside the United States, as well. By 2011, the estimated international market will be $1.8 billion dollars. The Techno Forensics Conference has increased in size by almost 50% in its second year; another example of the rapid growth in the market. This book is the first to combine cybercrime and digital forensic topics to provides law enforcement and IT security professionals with the information needed to manage a digital investigation. Everything needed for analyzing forensic data and recovering digital evidence can be found in one place, including instructions for building a digital forensics lab. * Digital investigation and forensics is a growing industry * Corporate I.T. departments needing to investigate incidents related to corporate espionage or other criminal activities are learning as they go and need a comprehensive step-by-step guide to e-discovery * Appeals to law enforcement agencies with limited budgets.
Email Forensics -- Developing a Digital Investigative/Electronic Discovery Capability -- Digital Forensics in a Multi Operating System Environment -- Digital Forensic Investigation Operations -- Balancing Records & Information -- Cyber Crime Investigations -- Windows and DVD Forensics -- Alternate Data Storage Forensics -- Buidling a Digital Forensics Lab.
Includes index.
Keywords: Computer crimes -- Investigation; Electronic discovery (Law); Electronic books